'It will not stop me or anyone like me': Women and Imprisonment in Ireland, c.1922-1947. - Byrne, Susan (Trinity College Dublin. School of Histories & Humanities. Discipline of History, 2024)
This thesis explores the experience of the female prisoner in the Irish justice system from c.1922-1947. It focuses on that group of women who made up the bulk of those imprisoned by the state -those convicted of relatively minor, non-violent offences, including larceny, drunkenness, and prostitution. Following the Irish revolutionary period, the transition from British to Irish control resulted in little to no change for prisoners held in Irish prisons, and developments in law and regulations relevant to the prisoners' experience were glacially slow. While there was much continuity in the prison system itself, between 1922 and 1947 there was a significant decrease in female prison numbers. Yet those women who were proceeded against were at least twice as likely to be imprisoned as men. This thesis explores why this was, suggesting that women¿s inability to pay fines played a major role. It examines crime statistics, the prison experience, how these women were treated by the courts, and what contemporary newspaper reporting reveals of prevailing social attitudes to female crime and female criminals. Between 1922 and 1923, the detention of women during the Civil War period reveals a twin-track approach to imprisonment for those imprisoned under normal judicial process and those committed under extra-judicial measures. These prisoners absorbed a huge amount of state energy and finance at a time when the new state was fighting for its very survival. Arguably, the existence of a significant number of political prisoners in the prison system undermined the position of the ordinary prisoner; it is at least clear that former experience as political prisoners did not lead politicians to prioritise prison reform. This study gives some insight into the lives of ordinary female prisoners: how they survived and how the system treated them. The case studies in the final chapter demonstrate the complexity of people¿s lives and some of the issues which led them to behave as they did: lack of employment, abuse of alcohol, emotional, personal and mental health difficulties, and lack of accommodation. These are issues which continue to play a role in the lives of female prisoners in the twenty-first century.
APPROVED
Keywords: women; prison; Free State; crime